Efektivitas Penggunaan Media Pembelajaran Digital Pada Hasil Belajar Siswa Kelas 5 SDN 6 Nagrikaler - Rosmana, Primanita Sholihah; Iskandar, Sofyan; Rahma, Ayang Ranisa; Maria, Salsa; Supriatna, Supriatna; Wahyuningtyas, Tri (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
Generations of the Nation is the hope of the state, services for Basic Education are the needs of the Indonesian people. This study aims to: 1) determine the effectiveness of digital learning media in improving student learning outcomes; 2) knowing students' knowledge before and after being given learning with digital learning media; 3) take advantage of advances in digital technology. On the other hand, this technological progress is very rapid and can be said to be a form of re-adaptation for teachers. The existence of Digital Learning media is a process to complement the needs of prospective generations to make it easier to learn, we cannot deny that when we are still using old learning media, children can get bored in learning. In short, we must take advantage of technological advances so that the demands of the nation's expectations can be fulfilled. Gols a teacher turns barren land into fertile land, the child is a layman who needs guidance and the teacher is a uswah who guides. Keywords; Learning Media, Learning Outcomes, Technology, Effectiveness.